Isolasi dan Karakterisasi Mutan sup45 Saccharomyces cerevisiae Sensitif Temperatur - Akhmaloka Akhmaloka; R. Hertadi; Senam Senam; P. E. Susilowati; M. Sindumarta; H. Sutedjo (Institut Teknologi Bandung, 2004)
One of the approachs to understand the structure-function of the gene is by studying its mutants. A few of sup45 ts mutants was isolated from Saccharomyces cerevisiae strain BSC483/1a induced by EMS. The concentration EMS of 1.5% (v/v) was found to be the most effective concentration on this study. Eight of sup45 ts mutants were selected from 515 allosupressor mutants. All of the mutants showed lower growth rate and maximum growth compared to that of the wild type. In addition of allosuppression phenotype, six of the mutant showed temperature sensitive and the other two exhibited temperature and paromomycine sensitive. Quantitation of an allosuppression phenotype using plasmid-borned gene fusion, PGK-termination codon-LACZ, showed that the mutants have a variation level of allosuppression. Temperature sensitivity analysis of the mutants showed that one, three, and one mutants were unviable at 32, 34, and 37OC, respectively. Further analysis on two of the mutants showed that the allosuppression level increased by increasing temperature growth. All the data suggested that the mutants were allelic specific mutants.